(untitled) (Vietnam Journal of Community Medicine, 2022)
Adenomatoid tumors of testis and epididymis is a benign tumor that is not uncommon. Many cases having orchiectomy were reported because there was no rapid histopathological test. Providing data on diagnosis, treatment, and treatment of the disease, we report a case of a 32-year-old man who diagnosed with Adenomatoid tummors of testis and epididymis at the Center for males and Sexual Medicine-Viet Nam-Germany University Hospital.